2022
DOI: 10.1002/fsn3.2703
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nostoc sphaeroids Kütz polysaccharide on renal fibrosis in high‐fat mice

Abstract: In this study, we investigated the effects of Nostoc sphaeroids Kütz polysaccharide (NSKP) on renal fibrosis in high‐fat mice. ApoE−/− male mice were randomly divided into four groups: control (Cont) group, high‐fat diet (HFD) group, HFD+0.4 g/kg BW NSKP, and HFD+0.8 g/kg BW NSKP (NSKP groups). The Cont was fed a standard diet. The HFD group was fed HFD. Every day, NSKP groups were fed HFD, as well as given 0.4 g/kg BW or 0.8 g/kg BW NSKP. After 22 weeks, the serum biochemical indices (TC, TG, LDL‐C, HDL‐C, GL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…As a critical exogenous risk factor, long-term consumption of HFD will inevitably lead to abnormal elevation of serum FA levels, which are further taken by renal tubules and stored as triglyceride, leading to renal tubular ELD . Emerging studies have shown that renal tubular ELD could cause lipotoxic damage to intrinsic renal tubular cells, following a pathology typified by hyperactivation of intracellular metabolic, oxidative, and inflammatory pathways that could ultimately provoke cell death. , Recently, several bioactive polysaccharides derived from natural products have been shown in evidence-based studies to be beneficial in countering HFD-induced metabolic disorders, including renal tubular ELD, , indicating that prolonged supplementation of such natural polysaccharides may be a beneficial strategy to reduce the risk of renal tubular ELD and CKD. Previously, we reported a homogeneous tea polysaccharide, TPS3A, with a strong potential to ameliorate HFD-exposed lipid metabolism disturbances in ApoE –/– mice .…”
Section: Discussionmentioning
confidence: 99%
“…As a critical exogenous risk factor, long-term consumption of HFD will inevitably lead to abnormal elevation of serum FA levels, which are further taken by renal tubules and stored as triglyceride, leading to renal tubular ELD . Emerging studies have shown that renal tubular ELD could cause lipotoxic damage to intrinsic renal tubular cells, following a pathology typified by hyperactivation of intracellular metabolic, oxidative, and inflammatory pathways that could ultimately provoke cell death. , Recently, several bioactive polysaccharides derived from natural products have been shown in evidence-based studies to be beneficial in countering HFD-induced metabolic disorders, including renal tubular ELD, , indicating that prolonged supplementation of such natural polysaccharides may be a beneficial strategy to reduce the risk of renal tubular ELD and CKD. Previously, we reported a homogeneous tea polysaccharide, TPS3A, with a strong potential to ameliorate HFD-exposed lipid metabolism disturbances in ApoE –/– mice .…”
Section: Discussionmentioning
confidence: 99%